2016
DOI: 10.11648/j.ajac.20160403.16
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Chemical Reactivity of <i>p</i>-aminophenyl Benzene-Fused Bis Tetrathiafulvalenes Through Quantum Chemical Approaches

Abstract: Abstract:The theoretical study on the molecular structure of a serie of p-aminophenyl benzene-fused bis tetrathiafulvalenes is presented. Optimized geometry of the title compound was calculated using DFT method at the level of B3LYP theory and 6-31G(d,p) basis set. The HOMO and LUMO analysis were used to determine the charge transfer within the molecule and some molecular properties such as ionization potential, electron affinity, electronegativity, chemical potential, hardness, softness and global electrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The quantitative description of the hardness (η) An N-electron device with total energy power E can be articulated as (16)…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative description of the hardness (η) An N-electron device with total energy power E can be articulated as (16)…”
Section: Methodsmentioning
confidence: 99%
“…e high stability and chemical inertness are due to the presence of high ionization energy. Global chemical descriptors like chemical potential, electrophilicity, hardness, softness, and electronegativity varies the chemical reactivity of the molecule [27][28][29][30]. All the calculated parameters indicate the high reactive nature of the grown sample.…”
Section: Frontier Molecular Orbitals (Fmos) Analysismentioning
confidence: 98%
“…Electrophilicity index (ω), which reflects the reduction of energy during the maximal flow of electrons between two systems 20 would show us whether the species is capable of charge donation. 21 As a thumb rule, a species with lesser 'ω' would be more reactive and nucleophilic and those with a higher value would go on to become a better electrophilic system. The studies revealed that DHCQ promises to be a better nucleophile while BDCQ showed a better propensity of an electrophile.…”
Section: Frontier Orbital Analysismentioning
confidence: 99%